Radiological study of the incidence of coxofemoral joint dysplasia in dogs using Norberg angle index method - Mehrnaz Dadashzadeh; Siamak Alizadeh (Veterinary and Comparative Biomedical Research)
Canine hip dysplasia is a joint laxity and osteoarthritis (OA) of the coxofemoral joints in dogs. The aim of this study was to investigate the incidence of hip dysplasia in suspected cases of the disease. A total of 91 litters of dogs with clinical signs of sacroiliac joint dysplasia referred to the Radiology Department of the Urmia Branch of the Faculty of Veterinary Medicine between April 2021 and June 2023 were examined using the Norberg angle radiography method. According to the results of this study, the incidence of this disease was higher in large breed dogs (90.55%) than in small breed dogs, and among large breed dogs, the highest incidence of this disease was observed in the German Shepherd breed (37.12%). The incidence of this disease in puppies under one year of age (55.12%) was higher than in other age groups, and the incidence in females (38.46%) was lower than in males. The bilateral form of this disease (89.25%) predominated over the unilateral form, and in the unilateral form, the left pelvic joint (60.15%) was more commonly affected than the right pelvic joint. The highest incidence of this disease has been observed in large breed dogs, but it has also been observed in medium and small breed dogs such as Shih Tzu, Pomeranian and Yorkshire Terrier. Primary complications of dysplasia of the sacroiliac joint include the development of osteoarthritis and/or degenerative joint disease, while secondary complications include displacement and subluxation of the sacroiliac joint. It is necessary to screen both male and female dogs for this disease prior to mating, and if positive, breeding should be prevented.